Mediators of increased blood flow in porcine skin - H. D. Moore; F. M. Cunningham (Mediators of Inflammation)
Nicotinates and benzalkonium chloride (B.Cl) cause inflammatory changes in human skin, thought to be dependent upon prostaglandin formation. This study has examined the effects of hexyl-nicotinate (HN) and B.Cl on blood flow in porcine skin. The role of prostaglandins and interleukin (IL)-1 in the blood flow response has been investigated. Blood flow was increased by both HN and B.Cl, the response to B.Cl being more protracted. Cyclooxygenase inhibitor pretreatment reduced these responses. IL-1-like biological activity was identified in normal porcine epidermis and the amounts recovered from inflamed skin were similar. Thus prostaglandin formation in HN or B.Cl-induced inflammation, if IL-1 dependent, is not associated with the loss of significant amounts of the cytokine from the epidermis.